The Role of Tropical Cyclones in Precipitation Over the Tropical and Subtropical North America - Dominguez, Christian; Magaña, Victor (Frontiers in Earth Science, 2018)
Tropical cyclones (TCs) are essential elements of the hydrological cycle in tropical and subtropical regions. In the present study, the contribution of TCs to seasonal precipitation around the tropical and subtropical North America is examined. When TC activity over the tropical eastern Pacific (TEP) or the Intra Americas Seas (IAS) is below (above-normal), regional precipitation may be below (above-normal). However, it is not only the number of TCs what may change seasonal precipitation, but the trajectory of the systems. TCs induce intense precipitation over continental regions if they are close enough to shorelines, for instance, if the TC center is located, on average, less than 500 km-distant from the coast. However, if TCs are more remote than this threshold distance, the chances of rain over continental regions decrease, particularly in arid and semi-arid regions. In addition, a distant TC may induce subsidence or produce moisture divergence that inhibits, at least for a few days, convective activity farther away than the threshold distance. An analysis of interannual variability in the TCs that produce precipitation over the tropical and subtropical North America shows that some regions in northern Mexico, which mostly depend on this effect to undergo wet years, may experience seasonal negative anomalies in precipitation if TCs trajectories are remote. Therefore, TCs (activity and trajectories) are important modulators of climate variability on various time scales, either by producing intense rainfall or by inhibiting convection at distant regions from their trajectory. The impact of such variations on water availability in northern Mexico may be relevant, since water availability in dams recovers under the effects of TC rainfall. Seasonal precipitation forecasts or climate change scenarios for these regions should take into account the effect of TCs, if regional adaptation strategies are implemented.